Increasing Student Learning Activeness Through the Problem Based Learning Model in PKN Subjects in Class IX of SMP Negeri 9 Sampit - Tini Puji Rahayu (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
This classroom action research was motivated by the low level of student learning activity, as seen from the large number of students who lacked responsibility for learning tasks, had difficulty expressing opinions and asking questions, had low levels of reading and writing activity, paid little attention to the teacher's explanations, and lacked the ability to train and apply their own abilities. Therefore, efforts are needed to implement learning models that are able to increase student learning activity, especially towards Civics learning. This classroom action research was carried out in two cycles, each consisting of four stages, namely planning, action, observation and reflection. In cycle I the number of students in the high activeness category began to increase, namely 72.73% of the total 33 students. Student learning activeness in cycle I had not yet reached the indicators of success, so the second cycle was implemented with several improvements to the shortcomings that occurred in cycle I. In Cycle II, the number of students with high category learning activeness had reached 84.85%. So in cycle II, students' learning activity had reached the indicator of success, because the number of students in the high learning activity category had exceeded 80%. This research proves that the application of the problem based learning model is able to increase student learning activity in Civics subjects in Class IX of SMP Negeri 9 Sampit for the 2023/2024 academic year